A Fibre Bragg Grating Sensor as a Receiver for Acoustic Communications Signals - Steven Hinckley; Graham Wild (Sensors, 2011)
A Fibre Bragg Grating (FBG) acoustic sensor is used as a receiver for acoustic communications signals. Acoustic transmissions were generated in aluminium and Carbon Fibre Composite (CFC) panels. The FBG receiver was coupled to the bottom surface opposite a piezoelectric transmitter. For the CFC, a second FBG was embedded within the layup for comparison. We show the transfer function, frequency response, and transient response of the acoustic communications channels. In addition, the FBG receiver was used to detect Phase Shift Keying (PSK) communications signals, which was shown to be the most robust method in a highly resonant communications channel.